Regulation of hippocampal postnatal and adult neurogenesis by adenosine A2A receptor: Interaction with brain‐derived neurotrophic factor. (7th June 2021) - Ribeiro, Filipa F.; Ferreira, Filipa; Rodrigues, Rui S.; Soares, Rita; Pedro, Diogo M.; Duarte‐Samartinho, Marta; Aroeira, Rita I.; Ferreiro, Elisabete; Valero, Jorge; Solá, Susana; Mira, Helena; Sebastião, Ana M.; et al.
Abstract: Adenosine A2A receptor (A2A R) activation modulates several brain processes, ranging from neuronal maturation to synaptic plasticity. Most of these actions occur through the modulation of the actions of the neurotrophin brain‐derived neurotrophic factor (BDNF). In this work, we studied the role of A2A Rs in regulating postnatal and adult neurogenesis in the rat hippocampal dentate gyrus (DG). Here, we show that A2A R activation with CGS 21680 promoted neural stem cell self‐renewal, protected committed neuronal cells from cell death and contributed to a higher density of immature and mature neuronal cells, particularly glutamatergic neurons. Moreover, A2A R endogenous activation was found to be essential for BDNF‐mediated increase in cell proliferation and neuronal differentiation. Our findings contribute to further understand the role of adenosinergic signaling in the brain and may have an impact in the development of strategies for brain repair under pathological conditions. Abstract : We showed that A2A receptor (A2A R) activation enhances hippocampal neurogenesis. This A2A R‐mediated neurogenesis was possible through an increase in the self‐renewal capacity of type 1 and type 2 cells, and through neuronal committed cell protection, neuronal differentiation, and neuronal branching. A2A R activation was shown to promote brain‐derived neurotrophic factor (BDNF) secretion and extracellular BDNF was essential for A2A R actions. Finally, A2A R endogenous activation was also essential for the BDNF‐mediated actions in neuronal differentiation but not for self‐renewal capacity.